Process Virtualization Theory and the Impact of Information Technology - Overby, Eric (Organization Science, 2008)
As the world becomes an increasingly virtual place, a growing number of processes are being conducted online or through other virtual means. Following such successes as electronic commerce (which is a virtualization of the physical shopping process) and ATM banking (which is a virtualization of the process of interacting with a human bank teller), there is increasing interest in the factors that make a process amenable (or resistant) to virtualization. This paper proposes process virtualization theory, which is a general theory that integrates and extends extant theory to explain which factors predict whether a process can be virtualized successfully. Recognizing that processes can be virtualized with or without the use of information technology, this paper makes explicit the theoretical significance of introducing information technology into process virtualization.